(x-2)3=64

Simple and best practice solution for (x-2)3=64 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-2)3=64 equation:


Simplifying
(x + -2) * 3 = 64

Reorder the terms:
(-2 + x) * 3 = 64

Reorder the terms for easier multiplication:
3(-2 + x) = 64
(-2 * 3 + x * 3) = 64
(-6 + 3x) = 64

Solving
-6 + 3x = 64

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 3x = 64 + 6

Combine like terms: -6 + 6 = 0
0 + 3x = 64 + 6
3x = 64 + 6

Combine like terms: 64 + 6 = 70
3x = 70

Divide each side by '3'.
x = 23.33333333

Simplifying
x = 23.33333333

See similar equations:

| 2x^2+36x-176=0 | | 6x^2-2x^2=2y^2 | | 2y+17=-4y-25 | | 8x+3x=180 | | -196x^2+676=0 | | f(x)=-x^2-4x+12 | | 9x-14-5x-3=0 | | f(5)=4cos(x)+-3sin(x) | | f(x)=4cos(x)-3sin(x) | | 8(t-5)+4t=6(2t+4)-13 | | y=0.15x+24.95 | | 2x+3x+2-114= | | 6x^2-7x=216 | | 46x=90+45+5-2 | | 5x-5=10x-15 | | 2x-3(-1)=13 | | tan(x-10)=1.2 | | -9(3b+1)+(28b-4)=0 | | k-29=0 | | 2s+30+3s+50=180 | | (9b-8)-2(4b+3)=-6 | | x+8=266 | | Y=(3x+4)(x+11) | | k^3+k^2+20k=0 | | 1.3q-5.8-0.4q=-0.1q-2.7 | | 5(13-3a)=-25 | | 6x+4x+4+8=7x+3+2x | | 4x+5+2x=31 | | -44=-8(-2x+4) | | 4x+2y-3z+a=14 | | -94=8r+3(6-8r) | | (2j+3)-4j-(j+3)= |

Equations solver categories